2015
DOI: 10.1007/s00508-015-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased gut microbiota diversity and abundance of Faecalibacterium prausnitzii and Akkermansia after fasting: a pilot study

Abstract: SummaryBackgroundAn impaired gut microbiota has been reported as an important factor in the pathogenesis of obesity. Weight reduction has already been mentioned to improve gut microbial subpopulations involved in inflammatory processes, though other subpopulations still need further investigation. Thus, weight reduction in the context of a fasting program together with a probiotic intervention may improve the abundance and diversity of gut microbiota.MethodsIn this pilot study, overweight people underwent a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 24 publications
(29 reference statements)
8
90
1
6
Order By: Relevance
“…Our findings are in line with the literature where Verrucomicrobia (mainly Akkermansia muciniphila ) exhibited an inverse relationship with body weight in mice31 and humans3233. Moreover, Verrucomicrobia were highly increased in undernourished neonatal mice26, fasted hamsters34, and fasted humans35. Whereas Verrucomicrobia are typical mucin-degraders29, Bifidobacteria , being well-known representatives of the phylum Actinobacteria, are able to convert diet and host derived carbohydrates29.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with the literature where Verrucomicrobia (mainly Akkermansia muciniphila ) exhibited an inverse relationship with body weight in mice31 and humans3233. Moreover, Verrucomicrobia were highly increased in undernourished neonatal mice26, fasted hamsters34, and fasted humans35. Whereas Verrucomicrobia are typical mucin-degraders29, Bifidobacteria , being well-known representatives of the phylum Actinobacteria, are able to convert diet and host derived carbohydrates29.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas Verrucomicrobia are typical mucin-degraders29, Bifidobacteria , being well-known representatives of the phylum Actinobacteria, are able to convert diet and host derived carbohydrates29. In malnourished children from Bangladesh25 and in AN patients from Japan13, no changes were observed in Actinobacteria whereas in fasting humans Bifidobacteria were also increased35. Notably, Bifidobacteria were in the core microbiome of AN patients but not in NW participants, implying that the vast majority of AN patients had specific bifidobacterial taxa in their microbiome in contrast to the healthy NW participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although, several beneficial associations have been found between A. muciniphila and metabolism, other reports have found among other bacteria a higher abundance of A. muciniphila in models of colon cancer [80]. Fasting and starving situations are associated with higher abundance of this bacterium [81,82], thus whether this association is involved in the etiology of such diseases or is the consequence of a change in dietary habits upon such pathologies required further investigations.…”
Section: Wwwmnf-journalcommentioning
confidence: 96%
“…This negative correlation might be associated with some confounders such as diet and medication. For example, food intake was greatly reduced in patients with colorectal cancer, while fasting is reported to be involved in increasing the level of A. muciniphila (Remely et al ., ,b). A small sample size of patients might be another influencing factor.…”
Section: Akkermansia Muciniphila Regulated the Balance Between Healthmentioning
confidence: 99%
“…Akkermansia muciniphila can significantly increase glucose tolerance and attenuate adipose inflammation in obese mice by inducing Foxp3 regulatory T cells (Shin et al ., ). With the application of probiotics to overweight subjects after fasting, an obviously increased level of A. muciniphila was observed (Remely et al ., ,b). Moreover, an interventional study with Akkermansia showed that the level of blood lipopolysaccharide, which functioned as an indicator of gut permeability, was significantly decreased in obese mice after the administration of Akkermansia (Everard et al ., ).…”
Section: Akkermansia Muciniphila Regulated the Balance Between Healthmentioning
confidence: 99%